Estratégias de produção comunicacional no ambiente de lojas de atacado fast fashion: a narrativa visual para o consumo no Megapolo Moda - Omine, Heloísa Kazuko (2015)
This project study investigates the narratives process, specifically how visual effects are presents in fast fashion system wholesale stores, in this study, stores located in Shopping Megapolo Moda, Brazilian first fashion specialized wholesale shopping. The subject of investigation presents the store environment as a space where images and stories can be constructed being part of a fashion obsolescence phenomena, in which the fashion system accelerates products renovation. All the same, the narratives created in this environment showing ephemeral or permanents scenarios can be studied displaying the fashion trends as a cause of this programed obsolescence. This study intend to demonstrate the visual merchandising as a results of a narrative structured plan, even if, not always prearranged as a chronicle. As a results, the study presents possibility for a method development for visual narratives that can be applied as a model for fast fashion wholesale stores.